The Influence of Parents' Role and Schools on The Learning Motivation of Class Students at SDN 091607 Sinaksak - Lenny Imelda Kristina Marbun; Natalina Purba; Lisbet N. Sihombing (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the role of parents and schools on the learning motivation of fifth grade students at SD Negeri 091607 Sinaksak. The method used in this research is the quantitative method. The sample used was 33 students, in the research there were: the dependent variable (x) student learning motivation, and the independent variable (y) the influence of the role of parents. The data collection technique is the test technique. Test results using the Hypothesis test technique with the help of the SPSS program, based on the results of a significance calculation of 0.000. Because significance is smaller than 0.05, H0 is rejected. Which means there is a significant influence between the school environment and the learning motivation of class V students at SD Negeri 091607 Sinaksak. n significant value for the relationship of variable (x) simultaneously to y is 0.00 < 0.05 and the f_count value is 27.947 > 4.20 (f table) so it can be concluded that the hypothesis test is accepted which means there is a relationship between variables (x ) simultaneously on the variable (y).